The The Difficult Case Consultation: An intervention for interprofessional health communication - Elissa Foster; Jay Baglia (Qualitative Research in Medicine & Healthcare)
An interprofessional group of healthcare practitioners sought a new approach to the early detection, prevention, and resolution of “difficult cases” in the inpatient care context. An action research project addressed this need by developing a narrative re-framing tool that helped reveal entrenched assumptions regarding the root causes of difficult cases in the hospital. The intervention method that emerged from the project — the Difficult Case Consultation (DCC) — is a theoretically-grounded process that helps teams to analyze and address complex communication problems in interprofessional healthcare contexts. Collaborative processes grounded in theory have proven to be the most successful when seeking to optimize healthcare team communication. The article describes the collaborative development of the DCC, presents two cases illustrating the process, and describes systemic factors that exacerbated the emergence of difficult cases in the inpatient context.